基于等温设计理论的湿式多片式制动器特性分析 - 朱霞; 冷志杰 (Jixie Chuandong, 2014)
In order to enhance and improve the accuracy of characteristics analysis of wet multdisc brake and avoid the local damage by high temperature and pressure on the brakes,the wet multiple of disc brake of wheel loader drive axle is considered as the research object,through the analysis of brake thermoelastic instability phenomenon and using design theory based on isothermal,a calculation method of brake characteristic on wet mult-disc brake is proposed.By the friction coefficient,the introduction of radial differences and other factors,the calculation equation of traditional village on the initial film pressure distribution is modified.The calculation accuracy of braking torque,the brake control force and the effective radius is further improved.The constraint equations of major design indicators based on the principle of isothermal wet brake is proposed.The results indicated that,this pressure distribution calculation model has a high calculation precision related to the pressure uniformly distributed calculat